Differences in the poly(ADP-ribosyl)ation patterns of ICP4, the herpes simplex virus major regulatory protein, in infected cells and in isolated nuclei. - Blaho, J A (1992)
Infected-cell protein 4 (ICP4), the major regulatory protein in herpes simplex viruses 1 and 2, was previously reported to accept 32P from [32P]NAD in isolated nuclei. This modification was attributed to poly(ADP-ribosyl)ation (C. M. Preston and E. L. Notarianni, Virology 131:492-501, 1983). We determined that an antibody specific for poly(ADP-ribose) reacts with ICP4 extracted from infected cells, electrophoretically separated in denaturing gels, and electrically transferred to nitrocellulose. Our results indicate that all forms of ICP4 observed in one-dimensional gel electrophoresis are poly(ADP-ribosyl)ated. Poly(ADP-ribose) on ICP4 extracted from infected cells was resistant to cleavage by purified poly(ADP-ribose) glycohydrolase unless ICP4 was in a denatured state. Poly(ADP-ribose) added to ICP4 in isolated nuclei was sensitive to this enzyme. This result indicates that the two processes are distinct and may involve different sites on the ICP4 molecule.